Pelatihan Pembuatan Proposal Usaha UMKM Untuk Karang Taruna Desa Mandala Mekar (TOT UMKM) - Harry Budiantoro; Imelda Sari; Nida Nadya Hasan; Hestin Agus Tantri Ningsih; Dinda Oktavia (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
MSME is an abbreviation for Micro, Small and Medium Enterprises. Basically, MSMEs are the meaning of enterprises or businesses carried out by individuals, groups, small business entities, or households. Indonesia as a developing country makes MSMEs the main foundation of the community's economic sector, this is done to encourage the ability of independence to develop in society, especially in the economic sector. Therefore, competent Human Resources (HR) are needed to produce quality financial reports. This activity is carried out through outreach, training and mentoring to MSMEs and youth organizations in Mandalamekar Village. Based on the PKM activities that have been carried out, there are participants who are able to understand 87% of the material. Apart from that, based on the practice of making business proposals, four financial reports were successfully prepared according to wishes and were able to be presented using a laptop, not manually as before. Significant managerial implications, especially in terms of increasing access to business capital. The following are several managerial implications that can be identified: the mentoring process will help MSME owners and managerial staff to increase their understanding of making business proposals properly and correctly.